(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The dynamic nature of language continually reflects developments in education, especially within the field of linguistics. This paper explores the emergence and categorization of neologisms—newly coined terms or expressions—related to educational practices, technologies, pedagogical approaches, and sociolinguistic changes. The study identifies and analyzes groups of neologisms that have arisen due to digital learning, inclusive education, interdisciplinary approaches, and globalization. It also considers how linguistic trends and societal needs influence the creation and acceptance of these terms. Understanding these linguistic innovations provides valuable insights into evolving educational paradigms and the role of language in shaping modern pedagogical discourse.